Strategi Pengembangan Wisata Bahari Kabupaten Morotai Provinsi Maluku Utara - Betly Taghulihi; Halida Nuria (Universitas Khairun, 2020)
Tourism as a service industry, plays a very important role in the national economy either as one source of foreign exchange, job creation, opening a business opportunity, even able to provide a very large multiplier effect for the national economy. there are 10 (ten) priority tourism destinations established by the government one of which is Morotai Island. Morotai Island is one of the districts located in North Maluku Province and is one of the largest islands in Malut which has abundant natural resources potential in agriculture, forestry, fishery and marine, mining and historical tourism potential especially places of historical relics of the second world war. This potential can be used as a mainstay sector that has good economic value in an effort to improve the welfare of Malut in general and morotai island community in particular. From the geographical aspect of Morotai island has a strategic position because it is on the lips of Asia Pacific trade route with administrative boundary as the north border of pacific ocean, west bordering with sulawesi sea, east bordering sea of halmahera, and south bordering strait morotai. Based on the above, it is necessary that the policies - policies that must be taken by the government and relevant stakeholders to determine internal and external factors in it so that it can formulate tourism development programs in Morotai Island, especially marine tourism. It is expected that the potential of marine tourism in the island of Morotai destinations developed in a long-term in order to become the economic support community of Morotai and for the advancement of tourism North Maluku Province.Keyword : development strategy, marine, tourism, Morotai